Impact of Structured Physical Exercise on Adolescent Depression: A Comprehensive Meta-Analysis of RCTs - De Moraes-Ferrari, G (BENTHAM SCIENCE PUBL, 2025)
Introduction Although research supports the benefits of Physical Exercise (PE) in treating adolescent depression, data remain limited regarding the most effective types, durations, and intensities of exercise. Moreover, most of the research conducted has focused on short-term outcomes, leaving a notable gap in understanding the long-term sustainability of these benefits. Evaluate the effectiveness of PE in alleviating depressive symptoms in adolescents diagnosed with major depressive disorder (CRD number: CRD42024585812). Methods The search was conducted from inception to July 2024 in the Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, PsycINFO, and SPORTDiscus. Randomized Controlled Trials (RCTs) involving adolescents aged 10-19 years diagnosed with unipolar major depression were included. The intervention group participated in structured PE programs, whereas the control group did not have PE. Two authors independently conducted screening, data extraction, and risk of bias assessment. A data synthesis was performed using a random-effects model to calculate the Standardized Mean Differences (SMD) for continuous outcomes. Heterogeneity was assessed using the I-2 statistic. Sensitivity and subgroup analyses were used to explore the effects of different PE modalities and the duration and intensity of the interventions. Results 13 RCTs: 759 adolescents in the PE group and 695 in the control group were obtained. PE significantly reduced depressive symptoms compared to the control (SMD=-0.55; p<0.01; I-2=61%). Aerobic exercise showed the largest effect (SMD=-0.69), followed by resistance training (SMD=-0.35) and whole-body vibration (SMD=-0.60). Moderate-intensity PE interventions lasting 30-60 minutes, 2-4 times/week, were associated with the greatest reductions in depressive symptoms. Discussion PE demonstrates considerable potential as an adjunctive strategy to pharmacological treatment for depression, suggesting its impact may be further enhanced when implemented alongside pharmacotherapy. Conclusion PE, aerobic exercise, and resistance training are effective interventions for reducing depressive symptoms in adolescents. Moderate-intensity exercise of 30-60 minutes offers substantial benefits.